Handbook of research on ICTs and management systems for improving efficiency in healthcare and social care - Cruz-Cunha, Maria Manuela, 1964-; Miranda, Isabel Maria, 1954-; Goncalves, Patricia, 1974-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book brings together a valuable research collection on ICT elements needed to improve communication and collaboration between global health institutes, public and private organizations, and foundations, highlighting the adoption and success factors in the development of technologies for healthcare"--Provided by publisher.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed July 16, 2013).
Keywords: Medical informatics -- Handbooks, manuals, etc; Management information systems -- Data processing -- Handbooks, manuals, etc; Information storage and retrieval systems -- Medical care -- Handbooks, manuals, etc; Health services administration -- Data processing -- Handbooks, manuals, etc; Medical Informatics; Telemedicine; Biomedical Technology; Developments and applications in healthcare; E-health; Healthcare in cloud computing; Public health; Social networks; Success factors; Telehealth systems; Electronic books